Children orphaned from COVID-19 in Thailand: maximize use of civil registration database for policies - Tangcharoensathien, Viroj; Iamsirithaworn, Sopon; Rittirong, Jongjit; Techanimitvat, Sanchai; Vapattanawong, Patama; Apiratipanya, Lucksana; Chanthama, Thiphaphon; Rueangsom, Putthipanya (Frontiers in Public Health, 2023)
Orphans, especially those who experience maternal loss at a young age, face significant long-term negative impacts on their lives and psychological well-being, extending beyond the age of 18. As of July 2023, the global death toll of COVID-19 has reached 6.9 million, leaving behind an unknown number of orphans who require immediate attention and support from policymakers. In Thailand, from April 2020 to July 2022, the total number of COVID-19-related deaths reached 42,194, resulting in 4,139 parental orphans. Among them, 452 (10.9%) were children under the age of five, who are particularly vulnerable and necessitate special policy attention and ongoing support. While the provision of 12 years of free education for all and Universal Health Coverage helps alleviate the education and health expenses borne by households supporting these orphans, the monthly government support of 2,000 Baht until the age of 18 is insufficient to cover their living costs and other education-related expenditures. We advocate for adequate financial and social support for COVID-19 orphans, emphasizing the importance of placing them with relatives rather than institutional homes. In the context of post-pandemic recovery, this perspective calls upon governments and global communities to estimate the number of orphans and implement policies to safeguard and support them in the aftermath of COVID-19.